Tailored immunotherapy approach with nivolumab with or without ipilimumab in patients with advanced transitional cell carcinoma after platinum-based chemotherapy (TITAN-TCC): a multicentre, single-arm, phase 2 trial - Grimm, Marc-Oliver; Grün, Barbara; Niegisch, Günter; Pichler, Martin; Roghmann, Florian Bernhard Gerhard; Schmitz-Dräger, Bernd Jürgen; Baretton, Gustavo Bruno; Schmitz, Marc; Bolenz, Christian; Foller, Susan; Leucht, Katharina; Schumacher, Ulrike; et al. (The lancet. Oncology, 2023)
Background - Nivolumab is used after platinum-based chemotherapy in patients with metastatic urothelial carcinoma. Studies suggest improved outcomes for dual checkpoint inhibition with high ipilimumab doses. We aimed to examine the safety and activity of nivolumab induction and high-dose ipilimumab as an immunotherapeutic boost as a second-line treatment for patients with metastatic urothelial carcinoma. - Methods - TITAN-TCC is a multicentre, single-arm, phase 2 trial done at 19 hospitals and cancer centres in Germany and Austria. Adults aged 18 years or older with histologically confirmed metastatic or surgically unresectable urothelial cancer of the bladder, urethra, ureter, or renal pelvis were eligible. Patients had to have progression during or after first-line platinum-based chemotherapy and up to one more second-line or third-line treatment, a Karnofsky Performance Score of 70 or higher, and measurable disease as per Response Evaluation Criteria in Solid Tumors version 1.1. After four doses of intravenous nivolumab 240 mg induction monotherapy every 2 weeks, patients with a partial or complete response at week 8 continued maintenance nivolumab, whereas those with stable or progressive disease (non-responders) at week 8 received a boost of two or four doses of intravenous nivolumab 1 mg/kg plus ipilimumab 3 mg/kg every 3 weeks. Patients who subsequently had progressive disease during nivolumab maintenance also received a boost, using this schedule. The primary endpoint was the confirmed investigator-assessed objective response rate in the intention-to-treat population and had to exceed 20% for the null hypothesis to be rejected (based on the objective response rate with nivolumab monotherapy in the CheckMate-275 phase 2 trial). This study is registered with ClinicalTrials.gov, NCT03219775, and is ongoing. - Findings - Between April 8, 2019, and Feb 15, 2021, 83 patients with metastatic urothelial carcinoma were enrolled and all received nivolumab induction treatment (intention-to-treat population). The median age of enrolled patients was 68 years (IQR 61-76), and 57 (69%) were male and 26 (31%) were female. 50 (60%) patients received at least one boost dose. A confirmed investigator-assessed objective response was recorded in 27 (33%) of 83 patients in the intention-to-treat population, including six (7%) patients who had a complete response. This objective response rate was significantly higher than the prespecified threshold of 20% or less (33% [90% CI 24-42]; p=0·0049). The most common grade 3-4 treatment-related adverse events were immune-mediated enterocolitis (nine [11%] patients) and diarrhoea (five [6%] patients). Two (2%) treatment-related deaths were reported, both due to immune-mediated enterocolitis. - Interpretation - Treatment with nivolumab and nivolumab plus ipilimumab boosts in early non-responders and patients who progress late significantly improved objective response rate after previous platinum-based chemotherapy compared with the rate reported with nivolumab in the CheckMate-275 trial. Our study provides evidence for the added value of high-dose ipilimumab 3 mg/kg and suggests a potential role for the combination as a rescue strategy in platinum-pretreated patients with metastatic urothelial carcinoma. - Funding - Bristol Myers Squibb.
Online verfügbar 28. Februar 2023, Artikelversion 27. März 2023
Gesehen am 23.05.2023